CISA Exam Prep - Gregg, Michael (Michael C.) (Pearson IT Certification, 2007)
CISA Exam Prep Certified Information Systems Auditor Michael Gregg Your Complete Certification Solution! The Smart Way to Study In This Book You'll Learn How To: Approach the IS audit process from ISACA's view of IS auditing best practices Relate and apply information security and systems audit best practices to the six CISA job practice areas Understand the IS audit process and learn how to apply best practices to secure an organization's assets Evaluate IT governance to ensure that the organization has the structure, policies, and mechanisms in place to provide sufficient IS controls Minimize risk within an IT/IS environment by using sound security techniques and practices Assess systems and infrastructure lifecycle practices to determine their effectiveness in meeting security requirements and meeting organizational objectives Gain a deeper understanding of the business continuity and disaster recovery process to help minimize risk Protect key informational assets by examining the security architecture and evaluating controls designed for the protection of confidentiality, availability, and integrity Streamline your exam preparations with our exam insights, tips, and study strategies WRITTEN BY A LEADING CISA EXAM EXPERT! Michael Gregg, founder and president of Superior Solutions, Inc., a Houston-based IT security consulting and auditing firm, has more than 20 years experience in information security and risk. He holds two associate degrees, a bachelor's degree, and a master's degree. He presently maintains more than a dozen certifications and is a nine-time winner of Global Knowledge's Perfect Instructor Award. Michael not only has experience in performing security audits and assessments, but also is the author of Que Publishing's Certified Ethical Hacker Exam Prep, CISSP Exam Cram, and is the co-author of Inside Network Security Assessment: Guarding Your IT Infrastructure by Sams Publishing.